2003
DOI: 10.1002/lsm.10226
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of lipopolysaccharides with phenothiazine dyes

Abstract: Toluidine blue interacts with LPS more significantly than methylene blue in vitro. This may be one of the main factors determining its greater photobactericidal efficacy against gram-negative bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
0
13

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 24 publications
5
67
0
13
Order By: Relevance
“…The present study continues our previous investigations of the interaction between the phenothiazine dyes, methylene blue (MB) and toluidine blue (TB), and gram-negative bacteria to clarify the differences in the photobactericidal efficacies of these dyes [1][2][3]. MB and TB are commercial phenothiazine dyes widely accepted in medical practice.…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…The present study continues our previous investigations of the interaction between the phenothiazine dyes, methylene blue (MB) and toluidine blue (TB), and gram-negative bacteria to clarify the differences in the photobactericidal efficacies of these dyes [1][2][3]. MB and TB are commercial phenothiazine dyes widely accepted in medical practice.…”
Section: Introductionsupporting
confidence: 61%
“…Previously we demonstrated that MB and TB readily form metachromatic complexes with LPS extracted from gram-negative bacteria [2]. It should be emphasized that not only does TB interact much better with LPS than MB, but TB also causes more bacterial photodamage [1,2].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations